THE INFLUENCE OF LOAN GROWTH, LOAN TO ASSETS, AND SIZE ON RETURN ON ASSETS THROUGH NON-PERFORMING LOANS IN BANKING COMPANIES - Dwitama, Aditya; Hasanudin, Hasanudin (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
Bank performance in the last 10 years has improved marked by an increase in loan growth but followed by a declining trend in profitability. Out of 47 banks, 28 were selected as samples using purposive sampling—data analysis techniques using IBM SPS Amos 24.0 software. From the results of data analysis, the results show that loan growth has a positive and insignificant effect on return on assets, loan to assets has a negative and insignificant effect on return on assets, size has a positive and significant effect on return on assets, loan growth and size have a positive and negligible effect on non-performing loans and loan to assets has a significant negative effect on non-performing loans. The results of mediation testing using the Sobel test, the results show that non-performing loans can provide a partial mediating role in the relationship between loan to assets and return on assets, but non-performing loans cannot act as mediation of the relationship between loan growth and size to the return on assets.